Explaining the increasing rates of blood feuds in post-communist Albania - Vodo, Teuta (Universite Libre de Bruxelles, 2014)
Since the regime collapse in 1991, Albania has been going through a democratization process. In contrast to government attempts to introduce a democratic system according to a western model, blood feuds based on Albanian customary law increased drastically and individuals began to seek their own justice by ignoring state and judicial institutions. The incidence of blood feuds increased exceptionally, not only compared with the situation under the communist regime but the crime rate in general. As a result, the Albanian state has appeared not only as weak and fragile but weaker in comparison with the previous communist regime. Although a great deal of research on vendetta is carried out either in the fields of anthropology or sociology of law, this topic has not been studied by political scientists. As a consequence, studies of vendetta in relation to institutional weaknesses are missing. Thus, one of the contributions of this study will be to fill this gap in the literature by explaining the role of state institutions in the continuation and increase in blood feuds. The Albanian case was chosen as a subject for study as it represents a country which following a harsh communist regime has made attempts at democratization with the aim of joining the European Union, and at the same time is characterized by the strong presence of customary law claiming revenge in cases of homicide, despite interventions by the judicial authorities. Therefore, the aim of this study is to explain the reasons for the increase in blood feuds in Albania from 1991 to 2010 by identifying the structure and agency factors impacting the motivation of individuals to commit murders in the name of vendetta. I will make use of historical institutionalism to identify the increasing returns of vendetta and explore the different factors and processes that trigger and underlie the institutional development of Albanian vendetta over time. Historical institutionalism is an approach to the analysis of the evolution of institutions and their outcomes in terms of formal and informal rules that shape the behavior of actors. Hence, understanding the causation and restraining factors in determining the high rates of blood feuds is indispensable. However, because of the lack of attention that historical institutionalism pays to the structure-agency dichotomy, the tools of criminology and more specifically, elements of ‘social control theory’ are required in this study. This theory enables/permits the study of vendetta by focusing on the motivation of the authors of vendetta, looking at the incidence and the forms of the criminal behavior. In order to explain vendetta and its causes, both fear of punishment (belief) and social bonds (attachment, commitment and involvement) have been taken into account. For this study, both primary and secondary sources were combined, such as expert interviews, archival documents and police data, in order to assess the cases of vendettas brought before the courts, judicial proceedings, and the final sentences handed down. The findings show that the weaker the bonds of trust in institutions such as state institutions and the legal system, the more individuals will be involved in blood feuds. The more trust is placed in institutions the less likely it is that individuals will be involved in vendetta. This research contributes to the literature dealing with institutional change and the study of crime rates in transitional democracies. === Doctorat en Sciences politiques et sociales === info:eu-repo/semantics/nonPublished